CREATIVE COLORING TECHNIQUES AS THE BASIS OF MODERN HAIRDRESSING DESIGN - Савіцька, О. В. (Art and Design, 2023)
The goal is to explore the main creative painting techniques, their types by technical and technological methods; to reveal visual and image features as determinants of fashion trends in the modern practice of hairdressing design in the world and in Ukraine. Methodology. The article uses visual-analytical analysis to process samples and written sources, typological analysis to identify criteria for the distribution of samples and their systematization, comparative analysis for visual-stylistic, constructive-compositional analysis of various hairstyles as a product of design. Results. The commonalities and differences of the main techniques of creative hair dyeing, which are divided by technological features into gradient segmental and stencil methods, are revealed. The results of their application are considered, which demonstrate the similarities and differences of the visual effect, in particular thanks to the techniques - pixel, footage, color blocking. The role of techniques and technologies in the formation of a design idea and a design project of a hairstyle, as well as the possibility of a result that affects the texture, color and constructive solution, which are decisive for the formation of an image/image, are revealed. Based on the analysis of hairstyle samples created by creative dyeing techniques, the approaches to their artistic and compositional solutions and design are summarized, and a classification of types of compositions as specific design solutions is made. Scientific novelty. For the first time, the characteristics of the main techniques and technologies of creative coloring as an object of design were formed: the features of artistic and compositional design solutions of hairstyles, created by applying the techniques of "pixel", "futuage", "color-blocking" were systematized; the leading trends in the development of specific types of creative painting, in particular futuage, in the world and in Ukraine were revealed. Practical significance. Based on the artistic analysis of creative hair dyeing, the trends of its development within the modern hairdressing art are revealed, the ideas of project solutions are presented the features of the product design in the hairdressing area are indicated, which, thanks to the knowledge of techniques and technologies, acquire highly aesthetic features, and at the same time significant customer demand.